2019
DOI: 10.1021/acs.jafc.9b03092
|View full text |Cite
|
Sign up to set email alerts
|

Oolong Tea Extract and Citrus Peel Polymethoxyflavones Reduce Transformation of l-Carnitine to Trimethylamine-N-Oxide and Decrease Vascular Inflammation in l-Carnitine Feeding Mice

Abstract: Carnitine, a dietary quaternary amine mainly from red meat, is metabolized to trimethylamine (TMA) by gut microbiota and subsequently oxidized to trimethylamine-N-oxide (TMAO) by host hepatic enzymes, flavin monooxygenases (FMOs). The objective of this study aims to investigate the effects of flavonoids from oolong tea and citrus peels on reducing TMAO formation and protecting vascular inflammation in carnitine-feeding mice. The results showed that mice treated with 1.3% carnitine in drinking water significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…14,16,32) Herein, our result demonstrated that TSGP as saponins-enriched fraction exerted the protective effect against L-carnitine-induced vascular endothelial damage, which was in accordance with previous investigation. 33) A similar report has shown that oolong tea extract or citrus peel polymethoxyflavones may decrease vascular inflammation in L-carnitine feeding mice by reducing TMAO formation and hepatic FMO3 mRNA levels. 34) Therefore, we speculate that the protective effects of TSGP on endothelial damage may be related to gut microbiota-derived TMAO formation of dietary L-carnitine ingestion in mice.…”
Section: Discussionmentioning
confidence: 89%
“…14,16,32) Herein, our result demonstrated that TSGP as saponins-enriched fraction exerted the protective effect against L-carnitine-induced vascular endothelial damage, which was in accordance with previous investigation. 33) A similar report has shown that oolong tea extract or citrus peel polymethoxyflavones may decrease vascular inflammation in L-carnitine feeding mice by reducing TMAO formation and hepatic FMO3 mRNA levels. 34) Therefore, we speculate that the protective effects of TSGP on endothelial damage may be related to gut microbiota-derived TMAO formation of dietary L-carnitine ingestion in mice.…”
Section: Discussionmentioning
confidence: 89%
“…Notably, dietary supplementation with resveratrol (a stilbenoid polyphenol) increased the abundance of Lactobacillus , reduced the levels of TMAO and attenuated the atherosclerosis phenotype of ApoE -/- mice fed a high-choline diet [ 167 ]. Flavonoids present in oolong tea extracts and citrus peel were reported to have similar Lactobacillus -boosting effects, accompanied by a reduction in the carnitine-induced increase in TMAO plasma levels in mice [ 168 ]. A recent double-blind randomized trial evaluating the TMAO-reducing efficacy of Taurisolo, a polyphenolic-rich pomace extract, found that it induced a significant reduction in TMAO relative to the placebo (63.6% vs. 0.54%) four weeks post-intervention [ 169 ].…”
Section: Potential Therapies In Choline-related Diseasesmentioning
confidence: 99%
“…In most animal experiments, high TMAO (0.12-0.3% of chow/drinking water) or L-carnitine or choline supplementation (≥1%) resulted in plasma levels between 30 and 100 µM [94,115,165,182,191,193], in some cases up to 400 µM TMAO [94,192], and many of these studies were conducted in female mice, which express high FMO3 and give rise to high TMAO concentrations in plasma. It should be noted that 1.3% L-carnitine in the diet of a mouse approximately corresponds to 2080 mg L-carnitine/kg (see calculation in the footnote of Table 2), which is an excessive dose, corresponding to a human equivalent dose of 11,818 mg L-carnitine/day [185].…”
Section: Unfavorable Effects Of Tmao In Animalsmentioning
confidence: 99%